KESANTUNANBERBAHASA MASYARAKAT KOTA PEKALONGAN ETNIK TIONGHOADALAM RANAH PERDAGANGAN - dan Alfons Oscar Christian, Sulis Adyana (Sasando, 2021)
This study describes the politeness of language in the ethnic Chinese community of Pekalongan City in the realm of commerce. The data in this study were collected using the observation method, while the data analysis was carried out using the ethnographic method. The form of obedience to the principle of language politeness in the Chinese ethnic Pekalongan City community in the realm of trade is in the form of a thimble rather than feeling, a thief of generosity, a thimble of approval, a thimble of approval, and a bidal of sympathy. Furthermore, the violation of the principle of politeness committed by the people of Pekalongan City, the ethnic Chinese in the realm of trade. The thimble whose politeness is violated is the thimble rather than feeling, the thimble of generosity, the thimble of approval, the thimble of humility, and the thimble of approval.